2017
DOI: 10.1007/s40544-017-0185-3
|View full text |Cite
|
Sign up to set email alerts
|

Design and application of friction pair surface modification coating for remanufacturing

Abstract: Friction, wear, and contact fatigue are the main causes of energy loss, material waste, and equipment failure. The aim of remanufacturing is to repair and modify the damaged equipment surface, and the surface coating is the major material that allows the remanufactured parts to be used in a new round of operation. Thus, the design and preparation of surface coatings are very important to repair, strengthen, or modify the friction pairs, in order to ensure long-term operation of the remanufactured parts. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Some of the coatings associated with superlubricity have been introduced in the superlubricity section and are not covered in detail again. Here, several new advances in tribological-related coating technology are briefly introduced, such as oxide coating [183][184][185][186], metal coating [187,188], composite coating [183,185,189,190], ceramic coating [191,192], and so on.…”
Section: Lubrication Of Surface Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the coatings associated with superlubricity have been introduced in the superlubricity section and are not covered in detail again. Here, several new advances in tribological-related coating technology are briefly introduced, such as oxide coating [183][184][185][186], metal coating [187,188], composite coating [183,185,189,190], ceramic coating [191,192], and so on.…”
Section: Lubrication Of Surface Coatingsmentioning
confidence: 99%
“…Wang et al [183,189] designed and prepared carbon nanotubes reinforced TiO 2 coatings, and found that a small content of CNTs could enhance the tribological properties of plasma sprayed ceramic coating remarkably, indirectly by influencing microstructure of coating and directly by tribo-effects of CNTs during tribotest, including structure strengthening, triboreorientation, tribo-protruding, tribo-film, and tribodefection as shown in Fig. 17.…”
Section: Lubrication Of Surface Coatingsmentioning
confidence: 99%
“…The most common causes of damage and failure of hydraulic actuators are three factors: abrasive wear, material fatigue, and friction [ 24 ].…”
Section: Failures Of Hydraulic Actuatorsmentioning
confidence: 99%
“…However, differing from oil/gas storage and transportation, the application of a biomimetic marine surface needs to focus on the marine environment and biological resource protection. Therefore, a new environmentally material or coating [121] will be the focus of research in the near future.…”
Section: Anti-icing Coatingsmentioning
confidence: 99%